Maqama of Ibn Abi Al-Khasal Al-Andalusi from a narrative and linguistic perspective - Jumaa, Dr.Karema Abed (Thi Qar Arts Journal, 2025)
The current research aims to study the representations of narrative and linguistic argumentation in the prose of Ibn Abi Al-Khasal Al-Andalusi, (465 AH - about 540 AH) taking the Maqama as the text of the research and the focus of its subject, by studying it analytically, based on the pragmatics concerned with signs and signals and the relationships between the sender/creator and the receiver/receiver, and the resulting persuasive and argumentative effects. One of the most important results of the research is that the linguistic and narrative argumentative representations came together and interconnected in a tight argumentative fabric with an intention that serves the theses embedded in the joints of the maqama